"Agency Problem" dan Keputusan Struktur Modal: Bagaimana Perusahaan Mengelola Utang dalam Rangka Meningkatkan Produktivitas, Nilai, dan Kinerjanya - Teddy Chandra (Jurnal Aplikasi Manajemen, 2010)
This article was aimed at describing the agency problem between investors and managers with solutional propositions and factors that affect capital structure as offered by the experts such as Modigliani and Miller, Myers, Jensen, and Brigham & Daves. A possible inference was proposed after explorating theories for solving the agency problem. Companies should enhance their managerial behaviour through asset growth strategy, potential growth strategy, and liquidity strategy in managing risks, particularly market risk. Thus, their productivity, performance, and value may be increased.